(untitled) (Bangladesh Journal of Nuclear Agriculture, 2025)
Salinity stress is a major constraint to rice production in the salt-affected coastal regions of Bangladesh. The study aimed to screen eighteen rice genotypes, including checks to find the potential genetic resources for salinity tolerance. A completely randomized design (CRD) with two replications was used at the reproductive stage under controlled conditions using a sustained water bath, where salinity levels ware maintained at 8, 10 and 12 dS/m following the standard IRRI protocol at the Bangladesh Institute of Nuclear Agriculture (BINA). Standard Evaluation Scoring (SES; 1-9 scale) was utilized to assess genotype responses. At 8 dS/m, eleven genotypes, including IRSSTN 1, IRSSTN 11, IRSSTN 21, BRRI dhan97, and Binadhan-10 exhibited strong tolerance. At 10 and 12 dS/m, IRSSTN 1, IRSSTN 11, BRRI dhan97, and Binadhan-10 consistently maintained superior performance. Genetic diversity was assessed using five SSR markers (RM336, RM585, RM1287, RM337, RM3412b), and cluster analysis based on Nei’s genetic distance grouped the genotypes into four distinct clusters. Notably, the genotypes identified as salt tolerant based on SES were also grouped together in the molecular clustering, indicating a genetic basis underlying their shared tolerance traits in breeding efforts. The integration of phenotypic and molecular data showed IRSSTN 1, IRSSTN 11, and IRSSTN 21 as promising candidates for developing salt tolerant rice varieties. These findings highlight the importance of using IRSSTN 1, IRSSTN 11, and IRSSTN 21 genotypes in future breeding programs aimed at improving rice resilience in saline environments. Bangladesh J. Nuclear Agric, 39(2): 49-62, 2025